2007
DOI: 10.1159/000112554
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cognitive and Functional Impairment in a Community Sample from São Paulo, Brazil

Abstract: Aims: To present the prevalence of cognitive and functional impairment (CFI) in community-dwelling elderly subjects from the city of São Paulo. Methods: The population was aged 60 years and older (n = 1,563; 68.7% women and 31.3% men) and lived in different socioeconomic areas. The following instruments were administered to the elderly: the Mini Mental State Examination and the Fuld Object Memory Evaluation. The Informant Questionnaire on Cognitive Decline in the Elderly and the Bayer-Activities of Daily Livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 59 publications
0
22
1
5
Order By: Relevance
“…A random sample (random selection of addresses obtained from our census) of 2,233 subjects older than 60 years was approached in the community, and a total of 1,563 subjects accepted to be visited by a trained interviewer. Interviewers obtained patient or caregiver informed consent, which was approved by the local research ethics committee, and administered the screening tests [13] . The tests included: the MMSE [14] , the Fuld Object Memory Evaluation [15] administered to the elderly; the Informant Questionnaire on Cognitive Decline in the Elderly [16] , the Bayer Activities of Daily Living Scale [17] administered to an informant.…”
Section: Methodsmentioning
confidence: 99%
“…A random sample (random selection of addresses obtained from our census) of 2,233 subjects older than 60 years was approached in the community, and a total of 1,563 subjects accepted to be visited by a trained interviewer. Interviewers obtained patient or caregiver informed consent, which was approved by the local research ethics committee, and administered the screening tests [13] . The tests included: the MMSE [14] , the Fuld Object Memory Evaluation [15] administered to the elderly; the Informant Questionnaire on Cognitive Decline in the Elderly [16] , the Bayer Activities of Daily Living Scale [17] administered to an informant.…”
Section: Methodsmentioning
confidence: 99%
“…The sociodemographic characteristics of the sample assessed at home have recently been presented in greater detail [8] : mean age was 71.4 years (range = 60-102; SD = 8.03), 83.5% with less than 80 years of age, 68.7% were female, 16.6% were illiterate, 71.0% had up to 8 years of schooling, 73.6% were classified as white and 15.6% as brown regarding skin color. According to the 2000 census [3] , the city of São Paulo had 88.4% of elderly with less than 80 years of age, 59.4% were female, 15.6% were illiterate, 80.0% had up to 8 years of schooling, 78.0% were classified as white and 13.3% as brown according to skin color.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Hototian et al reported a prevalence of 16% of cognitive impairment no dementia (CIND) in subjects over 60 years-old in Sao Paulo. 3 Chaves et al reported that the incidence of mild cognitive impairment, as defined by the Clinical Dementia Rating of 0.5, was 13.2 per 1000 elderly subjects per year. 4 In a clinical setting, we have recently shown that patients with multiple-domain amnestic MCI tend to be older and to have a worse cognitive performance than those with single-domain MCI (amnestic and non-amnestic), suggesting that the former subgroup may represent a more severe stage of MCI.…”
Section: Introductionmentioning
confidence: 99%